2015
DOI: 10.1158/1078-0432.ccr-14-2049
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Methylation of CDO1 Identifies Clear-Cell Renal Cell Cancer Patients with Poor Survival Outcome

Abstract: Purpose In this era of molecular diagnostics, prediction of clear-cell renal cell cancer (ccRCC) survival requires optimization, as current prognostic markers fail to determine individual patient outcome. Epigenetic events are promising molecular markers. Promoter CpG island methylation of cysteine dioxygenase type 1 (CDO1), which was identified as prognostic marker for breast cancer, is studied as a potential marker for ccRCC survival. Experimental Design We collected primary tissues of 365 ccRCC cases iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 31 publications
2
45
2
Order By: Relevance
“…Interestingly, in primary breast cancer, CDO1 hypermethylation did not correlate significantly with markers of tumor progression such as TNM factors, while CDO1 hypermethylation was the strongest independent prognostic factor . Importantly, the prognostic relevance of CDO1 methylation was confirmed even in a prospective nationwide cohort study in the Netherlands of patients with renal cell carcinoma . These findings suggest that the methylation status of the CDO1 gene could be used as a prognostic marker in various human cancers.…”
Section: The Best Performance As An Epigenetic Cancer Biomarker: Cdo1mentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, in primary breast cancer, CDO1 hypermethylation did not correlate significantly with markers of tumor progression such as TNM factors, while CDO1 hypermethylation was the strongest independent prognostic factor . Importantly, the prognostic relevance of CDO1 methylation was confirmed even in a prospective nationwide cohort study in the Netherlands of patients with renal cell carcinoma . These findings suggest that the methylation status of the CDO1 gene could be used as a prognostic marker in various human cancers.…”
Section: The Best Performance As An Epigenetic Cancer Biomarker: Cdo1mentioning
confidence: 92%
“…Since 2010, the frequent hypermethylation of the CDO1 gene has been reported in primary breast, 33,34 lung, 19 biliary tract, 35 esophageal squamous cell carcinoma (SCC) 36 and adenocarcinoma, 37 gastric, 19 colorectal, 19,38 bladder, 19 penile (SCC), 39 kidney, 40 prostate, 41 endometrial, 42 pancreatic 43 and gallbladder cancer. 44 The frequencies of the aberrations in CDO1 methylation in these cancers are high ( Figure 3A).…”
Section: The B E S T Performan Ce a S An Epi G Ene Ti C C An Cer B mentioning
confidence: 99%
“…Indeed, the variation among studies using different methods was not larger than among studies using the same method [14]. In addition, we have also shown that, if carefully aligned and optimized regarding genomic location and sensitivity, multiple DNA methylation assays can yield comparable results [16] and that DNA methylation markers can be validated in independent patient series using independent technologies [17,18].…”
Section: Editorial Lind and Van Engelandmentioning
confidence: 92%
“…118) and SLC16A3 (also known as MCT4) 119 . SLC16A3 encodes solute carrier family 16 member 3, a monocarboxylate transporter that is essential for transport of lactate across the plasma membrane, thus maintaining cellular pH and the appropriate progression of glycolysis 119 .…”
Section: Energy Homeostasis Vhl Met Flcn Tsc1 Tsc2mentioning
confidence: 99%